THE EFFECT OF IMPLEMENTING PROBLEM-BASED LEARNING ON THE FIFTH GRADE STUDENTS' HIGHER ORDER THINKING SKILLS ON HEAT AND TRANSFER THEME AT SDN KEPATIHAN 06 JEMBER - Sendy Darma Raga; Chumi Zahroul Fitriyah; Zetti Finali (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
The purpose of this study is to determine whether there is an effect of implementing problem based learning on the fifth grade students’ higher order thinking skills on heat and transfer theme at SDN Kepatihan 06 Jember and find out how much influence. This type of research was an experiment using a non equivalent control group design. The method used was a test to measure students' higher- order thinking skills. The samples of this study were 67 grade V students of SDN Kepatihan 06 Jember. Data were analyzed using the Levene test through SPSS software version 23 to determine the value of the t test. The results showed there was an effect of implementing problem based learning on the fifth grade students’ higher order thinking skills. The results of the test higher-order thinking skills were included in the medium category with an average score of 61.4 from a maximum score of 100. The categories of students' abilities from the scale of assessment of higher-order thinking skills diverse, namely students in the low category of 15 students, medium category 44 students, and 8 students high category.